The concept of KÆRLIGHED (love) as represented in data from Old Danish - Kacprzak, Aleksander (Folia Scandinavica Posnaniensia, 2021)
The article aims to reconstruct the conceptualization of KÆRLIGHED (LOVE) in Old Danish (1100–1515). In the first part of the study, the structure of the concept in Old Danish is analyzed, and parallels are drawn to the modern-day concept of KÆRLIGHED, the most significant differences being registered in the subcategories of PATRIOTISM and ROMANTIC LOVE, as well as in connection with the sense ‘love to do’. In the following parts of the study, the most important aspects and conceptual metaphors of Old Danish KÆRLIGHED are revealed, demonstrating a great influence of Christian values. Lastly, the nouns ælskhugh and kærlikhet are analyzed, and the difference between them is described as a different profiling of the various aspects of KÆRLIGHED, such as JOY and PLEASURE.